2019
DOI: 10.1111/jfs.12683
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, microbiological, and sensory characteristics of probiotic yogurt enhanced with Anethum graveolens essential oil

Abstract: In the present work, physicochemical, sensory characteristics and viability of Bifidobacterium bifidum and Lactobacillus casei of probiotic yogurt using dill (Anethum graveolens) essential oil (DEO) (50 and 100 ppm) were investigated at 4°C for 21 days. Alterations in amount of fat and protein of yogurt treatments during storage time were not significant. The viability of B. bifidum and L. casei increased up to the 2nd week of storage and then decreased by the end of the storage period. Generally, samples with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…Many ingredients have been added to yogurt in recent years, including Primula vulgaris (Lee et al, 2007), Mentha piperita, and Ziziphora clinopodioides (Sarabi-Jamab and Niazmand, 2009) to improve the nutritional, medicinal, and sensory properties and maintenance of yogurt. There are conflicting reports about the effecting of essential oils on the sensory properties so probiotic survival in yogurt, where some studies have shown a decrease in the sensory qualities of the yogurt (Moritz et al, 2015;Shahdadi et al, 2015), improved product properties sensory (Azizkhani and Parsaeimehr, 2018;Shahdadi et al, 2015), no adverse effect on probiotic activity (Azizkhani and Parsaeimehr, 2018;Sarabi-Jamab and Niazmand, 2009), and a negative impact on the activity and survival of probiotics (Azizkhani and Parsaeimehr, 2018). On the other side, the minimum inhibitory concentration (MIC) of plant essential oils against probiotics is high, while at the value of concentrations, the essential oils have inhibitory effects on pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Many ingredients have been added to yogurt in recent years, including Primula vulgaris (Lee et al, 2007), Mentha piperita, and Ziziphora clinopodioides (Sarabi-Jamab and Niazmand, 2009) to improve the nutritional, medicinal, and sensory properties and maintenance of yogurt. There are conflicting reports about the effecting of essential oils on the sensory properties so probiotic survival in yogurt, where some studies have shown a decrease in the sensory qualities of the yogurt (Moritz et al, 2015;Shahdadi et al, 2015), improved product properties sensory (Azizkhani and Parsaeimehr, 2018;Shahdadi et al, 2015), no adverse effect on probiotic activity (Azizkhani and Parsaeimehr, 2018;Sarabi-Jamab and Niazmand, 2009), and a negative impact on the activity and survival of probiotics (Azizkhani and Parsaeimehr, 2018). On the other side, the minimum inhibitory concentration (MIC) of plant essential oils against probiotics is high, while at the value of concentrations, the essential oils have inhibitory effects on pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that carvone (48.73%) and α‐phellandrene (31.71%) were the main agents. As indicated previously, the main chemical compositions of DEO are carvone and limonene (54.2 and 15.6%, respectively) (Singh et al 2011) and Mehdizadeh et al (2019) concluded that α‐phellandrene and carvone are the major agents in DEO (40.22 and 37.65%, respectively) that have some antimicrobial characteristics 4,20 . The amount of these compositions is related to weather and soil type, plant age, herbal drying procedure and extraction procedure (Table 1).…”
Section: Resultsmentioning
confidence: 77%
“…Therefore, it is better to use probiotic products include 10 6 CFU/mL of these kinds of bacteria every day and should be used every day 3 . All products including probiotic bacteria are recognized as ‘functional products’, and some probiotic foods are achieving universality and appropriate all over the developed country 4 . In these days, functional foods are limited mostly to cheese, yogurt and fermented milk drinks incorporated with probiotic bacteria like bifidobacteria and lactobacilli 5 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations